Internal Carotid Artery Occlusion as a Rare Presentation of Infectious Endocarditis: A Case Report - Thijs Wolf; Kayla Dewey; David Adler (Clinical Practice and Cases in Emergency Medicine, 2023)
Introduction: Internal carotid artery occlusion as a result of a septic embolism is a rare, commonly fatal, complication of mitral valve infectious endocarditis. Prompt recognition of this condition by the emergency physician may improve the chance of functional neurological survival. Case Report: A 50-year-old male presented minimally responsive with a right gaze deviation, left hemiparesis, and a score of 26 on the National Institutes of Health Stroke Scale. A point-of-care echocardiogram showed a large mitral valve vegetation, and computed tomography angiography demonstrated an internal carotid artery occlusion. Conclusion: The emergency physician should consider this potentially life-threatening condition and know the fundamental management recommendations once identified.